The influence of genetic factors on the severity of anxiety and depressive symptoms and the choice of coping strategies in reproductive tract cancer―a preliminary study - Anna Jurczak; Anita Chudecka-Głaz; Anna Michalczyk; Dorota Ćwiek; Joanna Owsianowska; Sylwia Wieder-Huszla (Frontiers in Public Health)
ObjectivesThe aim of this study was to analyze the impact of polymorphisms within the promoters of the MAO-A and the 5-HTT (SLC6A4) genes on the severity of anxiety and depressive disorder symptoms, and adaptation to the disease in patients with reproductive tract cancer.MethodsThis study involved a group female patients treated at the Department of Gynecological Surgery and Gynecological Oncology of Adults and Adolescents of the Pomeranian Medical University in Szczecin. The inclusion criteria for the study were advanced ovarian cancer or endometrial cancer, as well as treatment in the form of cytoreductive therapy and chemotherapy. The following standardized research tools were used to collect empirical data: Beck Depression Inventory, State–Trait Anxiety Inventory and Mini-Mental Adjustment to Cancer.ResultsThe study included 139 women diagnosed with endometrial cancer (63%) or ovarian cancer (37%). Assessment of the severity of anxiety and depressive symptoms in the studied group of patients depending on genotype did not show statistically significant differences. However, among patients with genotype MAO-A 4/4, the constructive style prevailed over the destructive one, and the most frequently chosen strategy was positive redefinition. In the case of patients with the 5-HTT gene polymorphism, the most frequently chosen strategies were anxious preoccupation and positive redefinition.ConclusionSearching for the relationship between genetic factors and the strategies adopted to cope with cancer requires intensive research. Undoubtedly, the severity of anxiety and depressive symptoms has an impact on adaptive behavior and the process of onco-logical treatment.